Moderate and Large Deviations for the Smoothed Estimate of Sample Quantiles. (11th June 2015) - He, Xiaoxia; Liu, Xi; Yao, Chun
Abstract : We derive the moderate and large deviations principle for the smoothed sample quantile from a sequence of independent and identically distributed samples of sizen .